TGF-β1-overexpressing mesenchymal stem cells reciprocally regulate Th17/Treg cells by regulating the expression of IFN-γ - Li Ruixue (De Gruyter, 2021)
Transforming growth factor (TGF)-β1 and mesenchymal stromal cells (MSCs) are two effective immunosuppressive agents for organ transplantation technology. This study aims to explore the molecular mechanism of TGF-β1-overexpressed MSCs on T cell immunosuppression. To achieve that, BM-MSCs were isolated from canine bone marrow, and their osteogenic differentiation and surface markers were detected. The TGF-β1 gene was transferred into lentivirus and modified MSCs (TGF-β1/MSCs) by lentivirus transfection. Furthermore, TGF-β1/MSCs were co-cultured with T cells to investigate their effect on differentiation and immune regulation. Results showed that TGF-β1/MSCs significantly downregulated the proportion of CD4+ CD8+ T cells in lymphocytes and significantly upregulated the proportion of CD4+ CD25+ T cells. Moreover, TGF-β1/MSCs significantly upregulated the expression of IL-10 in CD4+ T cells and downregulated the expression of IL-17A, IL-21, and IL-22. Meanwhile, interferon-γ (IFN-γ) neutralizing antibody blocked the effects of TGF-β1/MSCs on the differentiation inhibition of Th17. Overall, our results confirm the strong immunosuppressive effect of TGF-β1/MSCs in vitro and demonstrate that IFN-γ mediates the immunosuppressive effect of TGF-β1/MSC.